Der Cyborg: Diskurse zwischen Körper und Technik - Spreen, Dierk (Suhrkamp Verlag, 2010)
In this article, an idea of human cyborgs will be supported which still understands them to be "human" and which understands talking about cyborgs as a discourse and topical figure of reflective modernity. Now, at the same time this means that cyborgs undermine neither the linguistic or conceptual differentiation between the organic and the technological nor that between man and animal. What, however, becomes problematic are ways of human self-understanding and ideas of social relations which exclude the technological and the artificial from the description of the self, from physicality and the social or understand them only as additional factors.